2015
DOI: 10.1007/s00705-015-2460-9
|View full text |Cite
|
Sign up to set email alerts
|

Cymbidium chlorotic mosaic virus, a new sobemovirus isolated from a spring orchid (Cymbidium goeringii) in Japan

Abstract: Cymbidium chlorotic mosaic virus (CyCMV), isolated from a spring orchid (Cymbidium goeringii), was characterized molecularly. CyCMV isometric virions comprise a single, positive-strand RNA genome of 4,083 nucleotides and 30-kDa coat protein. The virus genome contains five overlapping open reading frames with a genomic organization similar to that of sobemoviruses. BLAST searches and phylogenetic analysis revealed that CyCMV is most closely related to papaya lethal yellowing virus, a proposed dicot-infecting so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Cymbidium chlorotic mosaic virus was isolated from spring orchid causing stunting and chlorotic streaks in Japan in 1996 (Kondo et al 1996). Molecular analysis of the virus revealed that it was a new monocot-infecting member of the genus Sobemovirus (Kondo et al 2015).…”
Section: Realm Riboviria Phylum Duplornaviricota Kingdom Orthornavira...mentioning
confidence: 99%
“…Cymbidium chlorotic mosaic virus was isolated from spring orchid causing stunting and chlorotic streaks in Japan in 1996 (Kondo et al 1996). Molecular analysis of the virus revealed that it was a new monocot-infecting member of the genus Sobemovirus (Kondo et al 2015).…”
Section: Realm Riboviria Phylum Duplornaviricota Kingdom Orthornavira...mentioning
confidence: 99%